EXISTENCE OF GENERAL COURSES: A STUDY OF ACEHNESE HISTORY AND CULTURE AS A COMPULSORY SUBJECT AT SAMUDRA UNIVERSITY - Usman, Usman; Akob, Bachtiar; Rahmatsyah, Rahmatsyah; Asnawi, Asnawi; Bukhari, Bukhari; Zulfiani, Zulfiani (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2023)
In the vision and mission of Samudra University "to become an independent and superior state university and prepare quality and competitive human resources". One of them is efforts to develop and improve the quality of general courses, including the history and culture of Aceh, in line with the Tri Dharma of Higher Education, including education, research, and community service. The aim is to prepare students to become members of society who have academic and professional abilities and are able to develop and create science and art, especially within the Samudra University environment. In accordance with Chancellor's Decree Number 95/UN54/M/2022 concerning the History and Culture of Aceh, it is a mandatory subject for students, with the principle of exploring and instilling the character values of Acehnese customs and culture according to sharia. This is closely related to the principle of Acehnese Specialty previously stated in Law Number 1/Missi/1959 in the fields of customs and culture, religion, and education. In the course of its history, after half a century, in 2000, the Implementation of Islamic Law was implemented in Aceh and confirmed by Qanun No. 9 of 2008 concerning the development of traditional life and customs, which describes actions and habits that have prevailed in society and are used as guidelines for daily life in Acehnese society. In line with these provisions, Samudra University empowers one of the general subjects: the history and culture of Aceh, which must be taken by every student so that they can improve quality and produce professional graduates at Samudra University. The method used is descriptive analysis with a qualitative approach. Researchers collect data through a literature review and analyse it using content or material analysis techniques. Stages of data analysis through data reduction techniques, data presentation, and drawing conclusions. In addition, the development of general subjects such as Acehnese history and culture can be implemented by lecturers independently. The use of course material can be used to introduce the historical heritage, customs, and culture of the Aceh Darussalam Kingdom to the Acehnese generation and students as academics on the Samudra University campus.